RADI-07. POSTOPERATIVE PAEDIATRIC CEREBELLAR MUTISM SYNDROME- IDENTIFYING QUANTITATIVE BIOMARKERS ON LONGITUDINAL FOLLOW-UP MRI. Issue 2 (22nd June 2018) - Avula, Shivaram; Spiteri, Michaela; Guillemaut, Jean-Yves; Windridge, David; Kumar, Ram; Pizer, Barry; Mallucci, Conor; Lewis, Emma
Abstract: BACKGROUND: Postoperative paediatric cerebellar mutism syndrome (POPCMS) is a complication affecting 8%-31% of children undergoing posterior fossa tumour resection. Injury to the proximal efferent cerebellar pathway during surgery is increasingly implicated in its causation but the exact pathogenesis remains unclear. Identifying MRI changes in the brain stem and cerebellum of these children can further the understanding of the pathogenesis and anatomical substrates involved. METHODS: Longitudinal analysis of follow -up MRI in 40 children with and without POPCMS following posterior fossa tumour resection was performed using a fully automated quantitative analysis of the brainstem and cerebellum in 3D space using the following steps: segmentation, registration, longitudinal interpolation of the MR images and machine learning techniques for feature selection and data classification. RESULTS: Longitudinal analysis and machine learning of the first 7 month MRI data following surgery identified six features at specific locations in Crus I, VI, VIIb, VIIb & IX of the anatomical right cerebellar hemisphere following surgery that are potential biomarkers of POPCMS. Three of these are identified at 1 month, two at 2 months and one at 5 months following surgery. CONCLUSION: This novel fully automated quantitative analysis of MRI in children following posterior fossa tumours resection reveals biomarkers that help to further the understanding the pathogenesis of POPCMS. This is one of the few studies that support the involvement of the right cerebellar hemisphere in the development of POPCMS. These biomarkers could also serve as imaging surrogates to the severity of the injury and prognosis.